Changes in body weight, health behaviors, and mental health in adults with obesity during the COVID‐19 pandemic. Issue 9 (19th July 2022) - Almandoz, Jaime P.; Xie, Luyu; Schellinger, Jeffrey N.; Mathew, M. Sunil; Marroquin, Elisa Morales; Murvelashvili, Natia; Khatiwada, Shreeya; Kukreja, Sachin; McAdams, Carrie; Messiah, Sarah E.
Abstract: Objective: The aim of this study was to examine the relationships between body weight changes, health behaviors, and mental health in adults with obesity during the second year of the COVID‐19 pandemic. Methods: Between March 1, 2021, and November 30, 2021, adults from three obesity practices completed an online survey. The primary outcomes were ≥ 5% of body weight change since March 2020 and associated health behaviors and mental health factors. Results: The sample ( n = 404) was 82.6% female (mean age 52.5 years, mean BMI 43.3 kg/m 2 ). Mean weight change was + 4.3%. Weight gain ≥ 5% was reported by 30% of the sample, whereas 19% reported ≥ 5% body weight loss. The degree of both weight gain and weight loss correlated positively with baseline BMI. Eighty percent of the sample reported difficulties with body weight regulation. Those who gained ≥ 5% versus those who lost ≥ 5% body weight were more likely to report higher levels of stress, anxiety, and depression; less sleep and exercise; less healthy eating and home‐cooked meals; and more takeout foods, comfort foods, fast foods, overeating, and binge eating. Conclusions: Weight gain in adults with obesity during the COVID‐19 pandemic is associated with higher baseline BMI, deteriorations in mental health, maladaptive eating behaviors, and less physical activity and sleep. Further research is needed to identify effective interventions for healthier minds, behaviors, and body weight as the pandemic continues. Abstract :